Resolving the intrinsic short-range ordering of K+ ions on cleaved muscovite mica - Franceschi, Giada; Kocán, Pavel; Conti, Andrea; Brandstetter, Sebastian; Balajka, Jan; Sokolović, Igor; Valtiner, Markus; Mittendorfer, Florian; Schmid, Michael; Setvín, Martin; Diebold, Ulrike (Nature communications, 2023)
Muscovite mica, KAl2(Si3Al)O10(OH)2, is a common layered phyllosilicate with perfect cleavage planes. The atomically flat surfaces obtained through cleaving lend themselves to scanning probe techniques with atomic resolution and are ideal to model minerals and clays. Despite the importance of the cleaved mica surfaces, several questions remain unresolved. It is established that K+ ions decorate the cleaved surface, but their intrinsic ordering - unaffected by the interaction with the environment - is not known. This work presents clear images of the K+ distribution of cleaved mica obtained with low-temperature non-contact atomic force microscopy (AFM) under ultra-high vacuum (UHV) conditions. The data unveil the presence of short-range ordering, contrasting previous assumptions of random or fully ordered distributions. Density functional theory (DFT) calculations and Monte Carlo simulations show that the substitutional subsurface Al3+ ions have an important role for the surface K+ ion arrangement.